Ecosystem Water Storage in a Teak Plantation under the Doi Tung Reforestation Royal Project, Chiang Rai Province, Northern Thailand - Sumanochitraporn, Samart; Khamyong, Soontorn; Anongrak, Niwat (วารสารวนศาสตร์ไทย, 2022)
The water storage in an ecosystem of a 22-year-old teak (Tectona grandis L.f.) plantation under the Doi Tung Reforestation Royal Project in Chiang Rai province was studied using five sampling plots, each of size 40×40 m2, which arranged randomly in areas of an altitude ranging between 515 and 704 m m.s.l. All individuals of teak and successional species of height >1.5 m were measured for stem girths at 1.3 m above ground (gbh) and tree heights. The mean densities of teak and successional species were calculated to be 85+48.73 and 23+38.38 trees plot-1, respectively. The average stem and height growths were measured at the following order: 63.87+7.85 cm and 16.62+3.12 m. The successional species in the five plots varied between 1 and 13 species. The average biomass of teak and successional species was 42.24+0.65 Mg plot-1 (264.0 +103.42 Mg ha-1), and contained the average water amount of 47.72+20.93 m3 plot-1 (298.25+130.82 m3 ha-1). The maximum capacity of waters storage in 2 m soil depth in the plantation was measured at 1,133.57+117.28 m3 plot-1 (7,084.81+ 733.0 m3 ha-1), whereas the water storage in rainy season (on 17thAugust 2013) was calculated to be 758.38+101.50 m3 plot-1 (4739.85+634.41 m3 ha-1, 66.90% of the maximum storage). The maximum water storage in the stand ecosystem (plant biomass and 2 m soil depth) was evaluated to 1,181.29 m3 plot-1 (7,383.06 m3 ha-1), while the water storage on 17th August 2013 was accounted to 806.10 m3 plot-1 (5,038.13 m3 ha-1, 68.24%). The percentage of water storage in plant biomass was only 4.04-5.92%, and the remained 94.08-95.96% were in the soil. The water storage in the teak plantation implied its ecological roles, and importance for restoring the watershed environment and the indirect benefits to highland and lower land communities since the water storage capacity can reduce the streamflow and flash flooding. Keywords: Ecosystem water storage, Doi Tung Reforestation Royal Project, Teak plantation